Climate change in Japan's new defence and security strategies - Cook, Alistair David Blair (2023)
Japan has taken concrete steps to integrate climate change into its defence and security strategy going forward, and to provide the necessary budget for implementing the relevant measures needed in mitigating the impacts of this threat. This may signal a more prominent leadership role for Japan on climate security in the Indo-Pacific.